Poligami dalam Al Quran Perspektif Penafsiran - Rahmat Syukri; Messy Precia; Laily Rahma Wati; Jendri Jendri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Polygamy in Islam is regulated with clear provisions based on the Qur'an and Hadith. Surah Al-Nisa/4:3 permits polygamy with a maximum of four wives, under the primary condition of fairness in fulfilling material needs such as food, clothing, and shelter. However, Surah Al-Nisa/4:129 emphasizes that emotional fairness, such as inclinations of the heart, cannot be mandated as it is beyond human capability. The Prophet Muhammad SAW exemplified how to practice polygamy while adhering to the principle of justice emphasized in Islam. Historically, the regulation of polygamy aimed to address social crises in early Islamic society, such as the high number of widows and orphans due to war. Polygamy was viewed as a social solution to protect the rights of women and children, albeit under strict conditions. In conclusion, polygamy in Islam is an option permitted only in specific circumstances, not an obligation or outright recommendation, with a strong emphasis on justice and the welfare of all parties involved.